Record Linkage Approaches Using Prescription Drug Monitoring Program and Mortality Data for Public Health Analyses and Epidemiologic Studies. Issue 1 (January 2020) - Nechuta, Sarah; Mukhopadhyay, Sutapa; Krishnaswami, Shanthi; Golladay, Molly; McPheeters, Melissa
Abstract : Background: The use of Prescription Drug Monitoring Program (PDMP) data has greatly increased in recent years as these data have accumulated as part of the response to the opioid epidemic in the United States. We evaluated the accuracy of record linkage approaches using the Controlled Substance Monitoring Database (Tennessee's [TN] PDMP, 2012–2016) and mortality data on all drug overdose decedents in Tennessee (2013–2016). Methods: We compared total, missed, and false positive (FP) matches (with manual verification of all FPs) across approaches that included a variety of data cleaning and matching methods (probabilistic/fuzzy vs. deterministic) for patient and death linkages, and prescription history. We evaluated the influence of linkage approaches on key prescription measures used in public health analyses. We evaluated characteristics (e.g., age, education, sex) of missed matches and incorrect matches to consider potential bias. Results: The most accurate probabilistic/fuzzy matching approach identified 4, 714 overdose deaths (vs. the deterministic approach, n = 4, 572), with a low FP linkage error (<1%) and high correct match proportion (95% vs. 92% and ~90% for probabilistic approaches not using comprehensive data cleaning). Estimation of all prescription measures improved (vs. deterministic approach). For example, frequency (%) of decedents filling an oxycodone prescription in the last 60 days (n = 1, 371 [32%] vs. n = 1, 443 [33%]). Missed overdose decedents were more likely to be younger, male, nonwhite, and of higher education. Conclusion: Implications of study findings include underreporting, prescribing and outcome misclassification, and reduced generalizability to population risk groups, information of importance to epidemiologists and researchers using PDMP data. Abstract : Supplemental Digital Content is available in the text.